PRESSURE-TEMPERATURE-DEFORMATION PATHS OF CLOSELY ASSOCIATED ULTRA-HIGH-PRESSURE (DIAMOND-BEARING) CRUSTAL AND MANTLE ROCKS OF THE KIMI COMPLEX: IMPLICATIONS FOR THE TECTONIC HISTORY OF THE RHODOPE MOUNTAINS, NORTHERN GREECE - Mposkos E.; Krohe A. (My University, 2006)
The ultra-high-pressure (UHP) Kimi complex (uppermost Eastern Rhodope Mountains) is a tectonic mixture of crustal and mantle derived associations. Pressure-temperature (P-T) paths and microtextural and geochronologlcal data reveal that crustal and mantle parts juxtaposed against each other at a depth corresponding to ~15 kbar (1 kbar = 100 MPa) had separate ascend histories. The crustal rocks comprise amphibolitised eclogites, orthogneisses, marbles, and migmatitic pelitic gneisses. The latter document UHP metamorphism within the dehydration-melting range of pelitic gneisses, with maximum P-T conditions of >45 kbar at ~1000°C, as determined by diamond inclusions in garnet and rutile needle exsolutions in Na-bearing garnet. Decompression was combined with only little cooling before 15 kbar, followed by more significant cooling between 15 and 10 kbar. This P-T path probably reflects ascent of UHP rocks within a subduction channel, followed by accretion in the lower crust of a thickened wedge. Although the first ascend phase was probably rapid, the overall time span for UHP metamorphism and final exhumation may have extended over more than 70 Ma. A U-Pb sensitive high-resolution ion microprobe (SHRIMP) age on zircons of ±149 Ma was suggested to date the UHP metamorphism, whereas Rb-Sr white mica and U-Pb zircon ages from syn-shearing pegmatites of ±65 Ma constrain medium- to low-grade shearing and final exhumation of UHP rocks. Mantle parts consisting of spinel-garnet metaperidotites and garnet pyroxenites reached maximum P-T conditions in the garnetperidotite field at T > 1200 °C and P > 25 kbar. This was associated with plastic flow and followed by severe near isothermal cooling to T < 800 °C at 15 kbar and static annealing. A garnet-clinopyroxene whole-rock Sm-Nd age from a garnet pyroxenite of ±119 Ma probably reflects the age of metamorphic mantle processes (static annealing following the high P/high T strain episode), rather than constraining the age of UHP metamorphism. © 2006 NRC Canada.